TABARAN: INTERCULTURAL EXCHANGE, PARTICIPATION AND COLLABORATION An analysis of the joint recording project of Not Drowning, Waving and the musicians of Rabaul, Papua New Guinea. (30th September 2015) - Webb, Michael
Abstract : Musical appropriation is a two-way traffic and elements from new musical vocabularies are assimilated by various parties for different ends. In this article I address issues involved in musical border crossing (and border repositioning) in the context of examining Tabaran, the musical collaboration between musicians of Rabaul, Papua New Guinea and the Melbourne musicians, Not Drowning, Waving (henceforth NDW), released early in 1991